TEACHER CREATIVITY IN INCREASING LEARNING MOTIVATION - Omah Mukarromah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
This study aims to describe the description of teacher creativity and solutions to foster teacher creativity in increasing learning motivation at SDN Drangong 1, Takakan District, Serang City, Banten Province. The approach used is a qualitative approach with descriptive methods. Data obtained from direct observation and analysis of reading materials or theories. Data were analyzed descriptively. The results of the study show that: (1) the creativity of teachers in developing methods, media and presentation of material, learning techniques at SDN Drangong 1 are not maximized; (2) the right form of teacher creativity can be carried out at SDN Drangong 1 namely developing the use of varied methods, appropriate media, presenting contextual material, giving praise and appreciating student work including creating creativity by learning through peers through visits between classes to find ideas just solving problems in class. The conclusion of the research is that developing creativity really helps teachers create a conducive academic environment in the learning process. High creativity for a teacher is necessary so that creativity is fully developed in all subjects. In the end students are motivated to learn. In fact, learning problems will continue and never stop, for this reason, teacher creativity continues to be developed.